The free vibrations analysis of the cupula in the inner ear using a natural neighbor meshless method - Santos, Carla F. (2022)
The cupula is a part of the inner ear semi-circular canals that plays an important role in the maintenance of the human balance. In order to understand the dynamic response of the cupula, first it is necessary to obtain its vibration frequencies. A two-dimensional and three-dimensional geometrical model of the cupula was built. Then, a free vibration analysis was performed using two distinct numerical techniques, the finite element method (FEM) and the natural neighbor radial point interpolation method (NNRPIM). Besides the fundamental analysis, other scenarios were studied, aiming to analyze the environment of the cupula (in healthy and pathologic scenarios). The results obtained with the geometrical models show that NNRPIM is capable to deliver results very close with the FEM. Additionally, the NNRPIM formulation possesses a high convergence and acceptable computational costs. This work presents for the first time a computational study on the free vibration analysis of the cupula and shows an alternative numerical technique to calculate with precision the natural frequency of the cupula. The outcomes of this work will allow the development of alternative therapies for cupulolithiasis, which causes severe dizziness.